RUSSIAN SCIENTIFIC DEGREES IN AGRICULTURAL SCIENCES IN THE LATE 19th AND EARLY 20th CENTURIES - O. Yu. Elina (Вавиловский журнал генетики и селекции)
This paper discusses the formation of the scientific appraisal system in high agricultural schools in the Russian Empire. Attention is focused on the activities of renowned professors I.A. Stebut, A.V. Sovetov, and D.N. Pryanishnikov, who were particularly active in propagation of high education and struggle for the right of the high agricultural school to confer master and doctor degrees in agricultural sciences.